Starstruck Bonds: Unveiling Celebrity Endorsement's Spell on Brand Love, with Friendship's Embrace as the Magic Touch - Gofur, Abdul; Shafariah, Hanuna (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2025)
This study aims to explore the influence of celebrity credibility in the context of celebrity endorsement on the formation of brand love and the role of friendship in moderating this relationship. Quantitative research methods were used, involving online surveys and structured interviews with consumers who have experience with brands that involve celebrity endorsements. Purposive sampling with a final 95 respondents participating in this research. PROCESS V3.5 for SPSS was chosen to analyze and test the hypothesis. The results of the analysis show that celebrity credibility has a significant influence on increasing brand love, and social influence plays an important role in strengthening the relationship between celebrity credibility and brand love. The practical implications of this study are the importance of selecting credible celebrities and using social interactions in marketing strategies to strengthen consumers' emotional ties to brands.